(3WQGR GdeLGdSs - (3SfOs; (3CHh YHO Gddg YHO GdQMef GHf GdbGSe GdeGdcj,J (B191 (3g` s
(3ChdgG (B:s
(3hSde bGd hbJ GdeZQH Edi Cf JZjH MeQI GdTab s
(3BNQgG (B:s
(3hbGd Hf MHjH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1644s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs